Why Have Trade Promotion Organizations Failed, and How Can They Be Revitalized? - De Wulf, Luc (World Bank, Washington, DC, 2012)
The proclaimed priority of exports contained in many development plans, Poverty Reduction Strategy Papers, and similar documents will remain hollow if it is not supported by forceful reforms that counter biases against exports. Once such reforms are implemented, much can be gained from reforming trade promotion organizations along the lines of the above recommendations -or from simply eliminating organizations that cannot be reformed.